Role of laparoscopy in reconstructive surgery - Rassweiler, Jens; Pini, Giovannalberto; Gözen, Ali S.; Klein, Jan; Teber, Dogu (Current opinion in urology, 2010)
Purpose of review - Despite increasing laparoscopic expertise in reconstructive surgery, open procedures still represent the gold standard. Robot-assisted techniques increasingly replace laparoscopy. However, laparoscopy is also developing: by improvement of ergonomics, new instruments, and techniques further reducing access trauma. We evaluated the actual role of laparoscopy focusing on main indications of urologic reconstructive surgery. - Recent findings - We analysed the current literature (PubMed/Medline) concerning indications, perioperative results, complications, and long-term outcome of laparoscopy for pyeloplasty, ureteral reimplantation, stone surgery, management of vesico-vaginal fistula, sacrocolpopexy (including evidence level). For all indications, laparoscopy provides the advantages of less postoperative pain, blood loss, shorter convalescence, and minimal disfigurement. However, it requires expertise with endoscopic suturing. Most experience (N > 1000) exists with laparoscopic pyeloplasty and sacrocolpopexy which can be considered as valuable options (IIB). Concerning ureteral reimplantation and repair of vesico-vaginal fistula, only a limited number of cases were reported (N < 150) (III). Laparoscopic stone surgery may gain importance particularly in developing countries. Robot-assistance will definitively increase the application of laparoscopic techniques providing optimal ergonomics, whereas the role of single-port surgery will be limited. - Summary - Laparoscopy will increasingly be used for reconstructive urologic surgery. This trend will be supported by the widespread use of the DaVinci device.
Gesehen am 10.05.2023